The Late Paleozoic - Early Mesozoic Chocolate Formation of southern Peru: new data and interpretations - Martínez Valladares, William (2005)
The Chocolate Formation is exposed in southern Peru between the cities of Nazca and Tacna, mostly in the Pacifie slopes of the Cordillera Occidental and along the coast. This lithostratigraphic unit was initially described near Arequipa by Jenk s (1948; "Volcànicos Chocolate"), who assigned a Jurassic age to it. It consists of a succession of volcanic rock s, sandstones, and con glomerates. Near the top of the unit, a Sinemurian ammonite was found in a fossiliferous limestone intercalation. In Tacna a similar unit was mapped as "Junera ta Formation" by Wilson & Gard a (1962) and later equated with the Chocolate Formation (Monge & Cerv antes, 2000). Recent studies have suggested that the base of this unit might be as old as Late Carboniferous (Pino et a l., 2004; Sempere et al., 2004). Because the Chocolate volcanism is likely to have been active in the middle Permian, it partly represents a coastal equivalent of the Mitu volcanism known in the Eas tern Cordillera.